The role of hedge funds in mergers and acquisitions. - Faizy, Suhail (2007)
ABSTRACT Since its inception, hedge funds have grown both in terms of number as well as size. This form of investment pool, which provides high returns at lower degree of risks and which is open only to few well informed investors is yet to undergo thorough research. This research has been undertaken to unfold a fairly new perspective of hedge fund activity, i.e. its involvement in mergers and acquisitions. Mergers and acquisition activity has been present from decades but has been given a new take from the time institutional investors have started playing an active role in it. Institutional investors are now known to be active corporate governance agents to bring about shareholder activism and monitor the role of the board of directors. But hedge funds for that matter are known to be a sophisticated pool of investors only recognized for their risk and return patterns, it would be interesting to learn whether they use corporate governance as a tool to manipulate the system or are actually taking a step towards orthodox investment strategies. The area under research being vast will restrict this work but will indeed help unfold few critical aspects of hedge fund involvement. Since there have not been many studies conducted in this area, this research will show a path for further work to be done.